Immortalizing Mesenchymal Stromal Cells from Aged Donors While Keeping Their Essential Features - María Piñeiro-Ramil; Rocío Castro-Viñuelas; Clara Sanjurjo-Rodríguez; Silvia Rodríguez-Fernández; Tamara Hermida-Gómez; Francisco J. Blanco-García; Isaac Fuentes-Boquete; Silvia Díaz-Prado (Hindawi Limited, 2020)
Human bone marrow-derived mesenchymal stromal cells (MSCs) obtained from aged patients are prone to senesce and diminish their differentiation potential, therefore limiting their usefulness for osteochondral regenerative medicine approaches or to study age-related diseases, such as osteoarthiritis (OA). MSCs can be transduced with immortalizing genes to overcome this limitation, but transduction of primary slow-dividing cells has proven to be challenging. Methods for enhancing transduction efficiency (such as spinoculation, chemical adjuvants, or transgene expression inductors) can be used, but several parameters must be adapted for each transduction system. In order to develop a transduction method suitable for the immortalization of MSCs from aged donors, we used a spinoculation method. Incubation parameters of packaging cells, speed and time of centrifugation, and valproic acid concentration to induce transgene expression have been adjusted. In this way, four immortalized MSC lines (iMSC#6, iMSC#8, iMSC#9, and iMSC#10) were generated. These immortalized MSCs (iMSCs) were capable of bypassing senescence and proliferating at a higher rate than primary MSCs. Characterization of iMSCs showed that these cells kept the expression of mesenchymal surface markers and were able to differentiate towards osteoblasts, adipocytes, and chondrocytes. Nevertheless, alterations in the CD105 expression and a switch of cell fate-commitment towards the osteogenic lineage have been noticed. In conclusion, the developed transduction method is suitable for the immortalization of MSCs derived from aged donors. The generated iMSC lines maintain essential mesenchymal features and are expected to be useful tools for the bone and cartilage regenerative medicine research.